Sistema productivo de hortalizas orgánicas como modelo de emprendimiento en sectores rurales de la zona de Babahoyo - López Zambrano, Lissette Carolina (2021)
This research deals with the production systems of organic vegetables as a model of entrepreneurship in rural sectors of the Babahoyo area. Vegetables are the consumer products in the majority of people's diets, therefore they deserve attention in terms of their production systems and how to influence entrepreneurship for the benefit of small farmers who grow it. Among the conclusions, it stands out that the production systems as a model of entrepreneurship in the Babahoyo area allow organic vegetable farmers to sell their products to the local markets; the ideal production system is the use of plant residues from crop stubble; At a general level, the appropriate production system is to use certified seeds, prepare the land by incorporating organic fertilizers, use organic pesticides based on plant waste and carry out cultural tasks manually in order to avoid contamination of the soil and the environment by external factors. ; it generates products that benefit health because chemical pesticides are not used for its production that cause deterioration in the environment; Most of the organic producers sell their products in the markets or in commissariats, there is no individual entrepreneurship model that allows them to obtain direct economic gains with the consumer; Organic production is linked to the most vulnerable sectors of the countryside, rural development programs and the fight against poverty, which could be strengthened with the incorporation of measures adopted by government agencies and Human beings have another opportunity to demonstrate their capacity. of ingenuity and creativity to sustain themselves as part of the planet's ecosystems. Until now, man has been able to defend himself from his natural enemies to remain on the face of the earth, the use of clean techniques such as organic agriculture are probably the best alternative to overcome current conditions.